Efficiency of Domestic and Foreign Banks in Thailand Since the Asian Financial Crisis - Chotigeat, Tosporn (Universiti Utara Malaysia, 2008)
During the 1990’s, two simultaneous phenomena had converged, greatly changing the financial services industry in Thailand. At the national level, Thai banks had to restructure in response to the financial reforms implemented as a result of the financial crisis of 1997. At the global level, large multinational banks were taking advantage of worldwide, financial deregulation and rapid technological advances by offering a full range of financial products and services in order to fiercely compete, both domestically and globally. Using quarterly financial time-series data of domestic and foreign banks in Thailand from 1997 to 2003, this paper seeks to analyze the cause of their efficiency. The findings indicate that both the efficiency ratio and loan loss provisions influenced the negative performance of domestic banks, while only loan loss provisions had negatively influenced the performance of foreign banks.